2021
DOI: 10.3126/jcmsn.v17i4.41887
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences of COVID-19 Survivors in Nepal: A Phenomenological Analysis

Abstract: Introduction: Novel coronavirus (COVID-19) is the new public health crisis rapidly threatening the world. A deeper understanding of these devastating lifetime experiences helps to develop a more complete picture of how holistic health may have been affected in survivors from pandemic. The objective of the study was to explore the lived experiences of COVID-19 survivors. Methods: A phenomenological qualitative research design was adopted following purposive sampling traced from the hospital record of Kosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
1
1
Order By: Relevance
“…In contrast to our findings the study held in Nepal entitled “Lived Experiences of COVID-19 Survivors in Nepal: A Phenomenological Analysis stated that, seven out of ten (7/10) of the participants reported responded feeling of stigmatizing responses and discrimination from health care workers during hospital stay [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings the study held in Nepal entitled “Lived Experiences of COVID-19 Survivors in Nepal: A Phenomenological Analysis stated that, seven out of ten (7/10) of the participants reported responded feeling of stigmatizing responses and discrimination from health care workers during hospital stay [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In this regard, the results of a qualitative showed that factors such as the incredible death statistics worldwide, the exacerbated physical exhaustion and symptoms, limited, defined drug protocol for treatment, and the low successful treatment rate lead to many patients affected by COVID‐19 equal to death and this issue negatively affect their psychological well‐being. False broadcasted information through social media and repeated news regarding the nature of disease and death plays an essential role in creating anxiety and fear among participants (Silwal et al., 2021 ). Another qualitative study showed that the feeling of being close to death is one of the most essential negative experiences of patients affected by COVID‐19.…”
Section: Discussionmentioning
confidence: 99%